Developing and evaluating the usability of a web-based Diabetic Retinopathy Health Education Program for patients with type 2 diabetes mellitus - Mat Isa, Rif’atunnailah; Chong, Mei Chan; Lee, Wan Ling; Iqbal, Tajunisah; Mansor, Mardiana; Zainudin, Airul Azizan; Saiful Suhardi, Mohd Iman (Saudi Arabian Armed Forces Hospital, 2023)
Objectives: To describe the development of a webpage based on the Intervention Mapping (IM) protocol and usability testing of the Diabetic Retinopathy Health Education Profram (DRHEP).